A systematic literature review of the use of formal methods in medical software systems. Issue 5 (27th February 2018) - Bonfanti, Silvia; Gargantini, Angelo; Mashkoor, Atif
Abstract: The use of formal methods is often recommended to guarantee the provision of necessary services and to assess the correctness of critical properties, such as functional safety, cybersecurity, and reliability, in medical and health care devices. In the past, several formal and rigorous methods have been proposed and consequently applied for trustworthy development of medical software and systems. In this paper, we perform a systematic literature review on the available state of the art in this domain. We collect the relevant literature on the use of formal methods for modeling, design, development, verification, and validation of software‐intensive medical systems. We apply standard systematic literature review techniques and run several queries in well‐known repositories to obtain information that can be useful for people who are either already working in this field or planning to start. Our study covers both quantitative and qualitative aspects of the subject. Abstract : The use of formal methods is often recommended to guarantee the provision of necessary services and to assess the correctness of critical properties, such as functional safety, cybersecurity, and reliability, in medical and health care devices. In this paper, we perform a systematic literature review on the available state of the art in this domain. We collect the relevant literature on the use of formal methods for modeling, design, development, verification, and validation of software‐intensive medical systems.